2019
DOI: 10.3390/genes10020085
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Marques, A. et al. Evolution of Plant B Chromosome Enriched Sequences. Genes 2018, 9, 515

Abstract: The authors wish to make the following modification in their review [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In Japan (RIKEN) using a 50 Ti beam energy of 80 MeV/A, two new neutronrich isotopes 31 Ne and 37 Mg were synthesized [22], and in the joint Dubna-RIKEN experiment with a 48 Ca beam at an energy of 70 MeV/A for the first time new isotopes 38 Mg and 40,41 A1 [23] were observed. Finally, in the 48 Ca fragmentation reaction on the accelerator of the University of Michigan, the last stable magnesium isotope, 40 Mg, was obtained [24]. All these experiments convincingly showed that the use of beams of neutron-rich nuclei makes it possible to obtain new isotopes in the reactions of fragmentation of the bombarding ion with yields several orders of magnitude higher than the corresponding yields in other reactions.…”
Section: Reactions Of Fragmentation Of Bombarding Ionmentioning
confidence: 81%
“…In Japan (RIKEN) using a 50 Ti beam energy of 80 MeV/A, two new neutronrich isotopes 31 Ne and 37 Mg were synthesized [22], and in the joint Dubna-RIKEN experiment with a 48 Ca beam at an energy of 70 MeV/A for the first time new isotopes 38 Mg and 40,41 A1 [23] were observed. Finally, in the 48 Ca fragmentation reaction on the accelerator of the University of Michigan, the last stable magnesium isotope, 40 Mg, was obtained [24]. All these experiments convincingly showed that the use of beams of neutron-rich nuclei makes it possible to obtain new isotopes in the reactions of fragmentation of the bombarding ion with yields several orders of magnitude higher than the corresponding yields in other reactions.…”
Section: Reactions Of Fragmentation Of Bombarding Ionmentioning
confidence: 81%